KAJIAN TENTANG INDEKS KECOCOKAN MODEL DALAM PEMODELAN PERSAMAAN STRUKTURAL BERBASIS KOVARIAN D ALAM LISREL DAN AMOS SERTA BERBASIS PARTIAL LEAST SQUARE DALAM PLS SEM - Umi Narimawati; Jonathan Sarwono (Universitas Komputer Indonesia, 2022)
The objective of this study is to review the goodness of fit (GOF) of Covariance and Partial Least Square Based Structural Equation Modeling using LSIREL, AMOS and Smart PLS. A method used is systematic secondary data search and meta - analysis. In this study, the present writer finds that there are some similarities and dissimilarities of the usage of each parameter used within the same parameter name; accordingly, users of those software must be able to distinguish each use of the parameter concerned in each software respectively in their researches Key Words : goodness of fit, SEM, LISREL, AMOS, SmartPLS